"Stain in life": the meaning of urinary incontinence in the context of Muslim postmenopausal women through hermeneutic phenomenology - Tengku Abdul Hamid, Tengku Aizan; Pakgohar, Minoo; Ibrahim, Rahimah; Dastjerdi, Marzieh Vahid (Elsevier, 2015)
Introduction: UI is a worldwide chronic condition among postmenopausal women. Little is known about the meaning of lived experiences of urinary incontinence of these women's viewpoints in their context. Objective: The aim of this study was to illuminate the experience of Muslim community-dwelling postmenopausal women who were living with urinary incontinence (UI). Methods: Seventeen women with UI (range: 52-68 years) who had experienced it for more than ten years were interviewed. A phenomenological hermeneutic method was used to analyze and interpret the interview texts. Results: The women's experiences of living with urinary incontinence have been presented in terms of three main themes: disruption of normal functioning, self-imposed restriction, and feelings of despair. Disruption of normal functioning meant emotional, spiritual, physical, and daily life disruption. Self-imposed restriction meant suppression of delights and needs and avoidance of social interactions. Feelings of despair referred to predictions of a bad and dark future of living with urinary incontinence, ambiguity, and hopelessness. The meaning of living with UI has been considered a 'stain in life'. Health care providers should be familiar with the different manifestations of urinary incontinence for early diagnosis and prevention of the negative effects of this condition to improve quality of life. In addition, symbolic interactionism theory can help health care providers to understand the meaning of urinary incontinence for women.